Uma arquitetura de sensoriamento remoto sensível ao contexto para irrigação - Boufleuer, Rafael (2015)
Considering that irrigation occupies the major percentage of consumed water in agriculture and that Brazil intends to expand considerably its irrigated area in the coming decades, there is a growing need in improving the irrigation water management, mostly in regions with limited availability of water or occurrences of hydric deficiency periods. Therefore, the increase of technologies for performing irrigation using environmental information is becoming important because they enable the maximization of water and energy consumption, maintaining or even improving the yield and quality of agricultural production. This work proposes a context-aware remote sensing architecture for irrigation and its contributions are: (a) the development of two prototypes of a moisture and precipitation meter based on the proposed architecture using open hardware technologies; (b) the development of a context taxonomy that defines the types of information that can be used in the prototype s architecture; and (c) a comparison between two different types of soil moisture sensors. For the validation of the architecture, two case studies were realized to verify the correct functioning of the architecture components, as well as a data collection was performed to make the comparison between a resistive low-cost sensor produced at the Federal University of Santa Maria, and a high-accuracy and high-cost frequency domain reflectometry (FDR) sensor (CS616 - Campbell Scientific, United States). The results obtained from the analyzed data were satisfactory, where it was verified that the architecture is viable, meeting the requirements to which it has proposed. In addition, the comparison performed showed a determination coefficient of up to 95 % between the low-cost resistive soil moisture sensors and the soil moisture sensors CS616 of Campbell R .